Lessons to be learned : Germany's crisis management in Mali (2013-2023) - Tull, Denis (2024)
Zusammenfassung: Germany was heavily involved in international crisis management in Mali for ten years, from 2013 to 2023. Important lessons can be drawn for effective and adaptive foreign and security policy, in particular concerning Germany’s internal structures and processes. Germany’s engagement in Mali was shaped by its commitments to allies and the United Nations. This was a legitimate interest, but left Berlin without strategic goals of its own in Mali. The lack of strategic and political orientation has resulted in less than optimal use of the very substantial resources invested. Interministerial cooperation failed to meet expectations, despite a number of new instruments (including in security force assistance) and institutional innovations (the Sahel Task Force, CIVAD). Although Germany’s participation in MINUSMA was operationally successful, it was inadequately anchored politically and strategically. MINUSMA as a whole failed to achieve its political goals. In the field of crisis management, Germany’s organisational learning processes occur mainly from one deployment to the next, less so during a given operation. Despite the duration of the Mali engagement, learning and adjustment processes occurred only at the operational-tactical level. Fundamental course corrections were not made, despite the obvious need to do so. Interministerial cooperation was insufficient to facilitate effective strategy-building. The learning culture within and between government departments proved inadequate